1979
DOI: 10.1177/1077727x7900700606
|View full text |Cite
|
Sign up to set email alerts
|

Body Proportions of Fashion Illustrations, 1840–1940, Compared with the Greek Ideal of Female Beauty

Abstract: Comparisons of the body proportions of the Greek ideal of female beauty with mean body propor tions of fashion figures of costume silhouette periods, 1840 through 1940, revealed that fashion illustrators in general have not adhered to the Greek ideal over time. In addition, comparisons of mean body proportions as well as the popular types of hair styles, face shapes, and shoulder slopes of sketched figures from three periods of stable costume silhouettes and two periods of transition from one silhouette to ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The greatest fluctuations were evidenced in the location of the secondary, or lower, waist/hip line during the months of 1923 and 1924. These results lend support to the concept that fashion illustrators tend to vary human body proportions to emphasize, or exaggerate, characteristics of a new style (Creekmore and Pedersen, 1979). (Allen, 1931 Weeden (1977), an analysis of correlation was undertaken to determine the degree of relationship among the three variables of hemline location, uppermost waist/hip location, and secondary waist/hip location.…”
mentioning
confidence: 62%
“…The greatest fluctuations were evidenced in the location of the secondary, or lower, waist/hip line during the months of 1923 and 1924. These results lend support to the concept that fashion illustrators tend to vary human body proportions to emphasize, or exaggerate, characteristics of a new style (Creekmore and Pedersen, 1979). (Allen, 1931 Weeden (1977), an analysis of correlation was undertaken to determine the degree of relationship among the three variables of hemline location, uppermost waist/hip location, and secondary waist/hip location.…”
mentioning
confidence: 62%
“…Elizabeth Lowe (1984) used this same approach to data collection in her study of the adherence of women's evening apparel styling to aesthetic rules. Creekmore and Pedersen (1979) also used a combination of ratio and nominal measures to study body proportions in fashion illustrations from 1840 to 1940 as compared to the Greek ideal. In order to study the changing hemlines in women's clothing, Richards measured from "mouth to skirt hemline, from mouth to uppermost waist/hip horizontal line, and from mouth to next lower waist/hip horizontal line" (p. 43), provided a lower or secondary waist/hip horizontal line was evident.…”
Section: Ratio Measurementmentioning
confidence: 99%
“…Certain features of dress may lend themselves to nominal measurement only, which is probably why researchers using higher levels of measurement (e.g., ratio scales) in the coding procedure often incorporate nominal measures as well (Creekmore & Pedersen, 1979;Littrell & Evers, 1985;Richards, 1983-84). For example, the style name of a garment component (e.g., a "bertha" style collar), a type of embellishment used (e.g., embroidery), or the mere presence of a component (e.g., sleeved versus sleeveless) can only be identified and nominally categorized.…”
Section: Feature Identification Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Horn and Gurel (1981) have explained the ideal Greek figure. Creekmore and Pedersen (1979) investigated body proportions used for fashion illustrations in 1840–1940 and compared them with the Greek ideal of female beauty. They found that the proportions in fashion illustrations had not adhered to the Greek ideal over time.…”
Section: Introductionmentioning
confidence: 99%